Building with Nature & Beyond Principles for designing nature based engineering solutions - H. Slinger, Jill (TU Delft Open, 2021)
This book is based upon the edX MOOCs Engineering: Building with Nature and Beyond Engineering: Building with Nature. The Engineering: Building with Nature MOOC, explores the use of natural materials and ecological processes in achieving effective and sustainable hydraulic infrastructure designs, distilling Engineering and Ecological Design Principles. In the Beyond Engineering: Building with Nature course, the missing element of Social Design Principles is developed and taught.